On the first philosophical use of alétheia as a discovery or illumination - González Fernández, Enrique (Logos. Anales del Seminario de Metafísica, 2024)
According to Julián Marías, it was Ortega, in 1914, who made the first philosophical use of the Greek word alétheia with the meaning of discovery or lighting: this is a significant innovation because Ortega introduced a new meaning, using that word, to overcome the idea, which seemed unacceptable to him, that truth has to be adequation. After Ortega, other philosophers, starting in 1927 with Heidegger, do not know where the etymological interpretation that they give as obvious for their philosophical reflections on truth comes from. In reality, there are no clear Greek texts that interpret the concept of alétheia either etymologically or philosophically. Julián Marías discovered the oldest etymological discussion in the linguist and philosopher Teichmüller (1879), which Ortega used as early as 1914 to make the first philosophical interpretation of that word. Despite this, it has become widely believed that Heidegger was the first to deal with truth as alétheia as opposed to what he calls the traditional concept of truth.
Keywords: adequation; alétheia; apocalypse; discovery; interpretation; lighting; mission; revelation; truth; unveiling